2021
DOI: 10.1039/d1nr02921e
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy and surface plasmon resonance for real-time single-cell monitoring of bacteriophage-mediated lysis of bacteria

Abstract: The growing incidence of multidrug-resistant bacterial strains presents a major challenge in modern medicine. Antibiotic resistance is often exhibited by Staphylococcus aureus, which causes severe infections in human and animal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The lysin-biofilm removal process is, however, indistinguishable but evident in the curve (i.e., a weak signal resulting in a 6-degree decline from 20 to 35 min). This decline may be caused by lysed bacterial clusters that are still covered on the SPR chip as previously reported ( Obořilová et al, 2021 ) and observed by SEM in Supplementary Figure 2 . In the SEM result, further lysis results in destruction of the biofilm which may characterize stage III of the sensogram.…”
Section: Discussionsupporting
confidence: 74%
“…The lysin-biofilm removal process is, however, indistinguishable but evident in the curve (i.e., a weak signal resulting in a 6-degree decline from 20 to 35 min). This decline may be caused by lysed bacterial clusters that are still covered on the SPR chip as previously reported ( Obořilová et al, 2021 ) and observed by SEM in Supplementary Figure 2 . In the SEM result, further lysis results in destruction of the biofilm which may characterize stage III of the sensogram.…”
Section: Discussionsupporting
confidence: 74%
“…The enzyme kills a wide range of clinical isolates of S. aureus , including MRSA, and lyses both coagulase-positive and coagulase-negative strains . Using SEM and AFM analysis, it is clear that lysostaphin treatment causes nanoscale perforation, formation of spheroplasts and protoplasts, followed by cell swelling and complete cell lysis (Figure B). This enzyme is active against cell wall fragments, heat-inactivated cells or viable cells regardless of their metabolic state or encapsulation conditions. , In addition, lysostaphin can disrupt the biofilms of S. aureus , although the effect varies with conditions used for biofilm formation. ,− This enzyme is unable to kill intracellular S. aureus due to its inability to enter mammalian cells, , which is nonetheless challenged by a very recent study showing that lysostaphin alone killed intracellular S. aureus to a great extent in several cell lines in a dose-dependent manner …”
Section: Introductionmentioning
confidence: 99%